Uma ferramenta para a customização de ambientes virtuais para práticas de Orientação e Mobilidade - M. Júnior, José Martônio L. de; Araújo, Mariana da C. Carneiro; Façanha, Agebson R.; Viana, Windson; Sánchez, Jaime (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
People who are blind (PwBs) can encounter barriers when doing tasks that require spatial representation (e.g., discerning the spot they are in, establishing the position of people and objects in a physical space, determining a direction to follow). Orientation and Mobility (O&M) is a special education area in which teachers nurture the development of PwBs’ abilities such as space recognition, self-protection, and mind maps building about their surroundings. Following researchers that include virtual environments in the O&M learning process, this paper brings a report about the research and development of a map editor and a mobile application. Together, these tools allow teachers to model and customize experiences for teaching O&M in indoor locations.